2013
DOI: 10.1016/j.ijrobp.2012.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Investigation of Adaptive Functioning Following Conformal Irradiation for Pediatric Craniopharyngioma and Low-Grade Glioma

Abstract: Purpose Children treated for brain tumors with conformal radiation therapy experience preserved cognitive outcomes. Early evidence suggests that adaptive functions or independent living skills may be spared. This longitudinal investigation prospectively examined intellectual and adaptive functioning during the first 5 years following irradiation for childhood craniopharyngioma and low-grade glioma (LGG). The effect of visual impairment on adaptive outcomes was investigated. Methods and Materials Children wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 20 publications
4
37
0
Order By: Relevance
“…Mean IQ and BRIEF scores were within the average range, indicating some preservation of function following CRT, which is consistent with prior findings (Netson, Conklin, Wu, Xiong & Merchant, 2013; Netson, Conklin, Wu, Xiong & Merchant, 2012; Conklin et al, 2008). IQ was not directly correlated with parent- or child-reported HRQoL.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Mean IQ and BRIEF scores were within the average range, indicating some preservation of function following CRT, which is consistent with prior findings (Netson, Conklin, Wu, Xiong & Merchant, 2013; Netson, Conklin, Wu, Xiong & Merchant, 2012; Conklin et al, 2008). IQ was not directly correlated with parent- or child-reported HRQoL.…”
Section: Discussionsupporting
confidence: 90%
“…This method has the potential to improve functional outcomes, although some cognitive functions may still be vulnerable (Conklin et al, 2008; Netson et al, 2012; Conklin et al 2012; Netson et al, 2013). While multiple studies have examined HRQoL after conventional radiation therapy, proton beam radiation therapy, chemotherapy, and other treatment modalities (Reimers et al, 2009; Laffond et al, 2012; Benesch et al, 2009), no known studies have examined HRQoL after CRT for pediatric brain tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Two previous reports suggested that patients treated for craniopharyngioma did not have significant long-term changes in IQ, daily living skills, or self-reported quality of life indicators. 26,31 . Future studies including the use of formal neurocognitive testing are warranted and ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies have reported that these children are acquiring intellectual and adaptive skills at a slower rate relative to their same age peers but are not losing skills over time (Netson, Conklin, Wu, Xiong, & Merchant, 2013;Palmer et al, 2001). By the time individuals are reaching adulthood, there are increased demands on and expectations of rapid development of cognitive abilities and independent living skills, but young adult survivors may experience more significant impairments relative to peers who are gaining these skills.…”
Section: Introductionmentioning
confidence: 99%